Productivity Growth in the United States and Germany: Is Germany Falling Further behind? - Georg Erber; Ulrich Fritsche (Weekly Report, 2005)
The long-term development in productivity in an economy is the main indicator in an assessment of the outlook for economic development. In theory, countries that lag behind the leading countries in productivity should gradually succeed in closing that gap. Since the mid-1990s the Federal Republic of Germany has not been able to continue the process of catching up with the trend in productivity in the United States that was typical until then. In past decades the development in Germany compared with the United States was dominated by the process of introducing best-practice technologies, for example modern information and communications technologies, but that has evidently faltered now. That is still the conclusion to be drawn after the introduction of the new methods of calculating the national accounts, which were expected to reduce the methodological differences in the assessment of productivity between Germany and the United States. However, the gap in productivity growth between the two economies may be expected to shrink again in the medium term, partly because the structural reforms on the labour market and the investment in modern information and communications technologies made in the past should have a positive effect. Productivity growth matters in the long run. As only the wealth created can be distributed the speed at which the efficiency of an economy is increasing will mark the limit for this distribution. So without a clear rise in efficiency the population in a country cannot expect their material prosperity to continue to rise. Owing to this fundamental interrelation determining the medium to long-term growth rate in productivity, and here especially the productivity of labour, is of crucial importance. Since the mid-1990s the typical process of catching up with the development in productivity in the United States has been interrupted in Germany. Until now economists have always assumed that a country with a lower level of productivity will be able to catch up owing to cost advantages in the acquisition of more efficient production technologies. By introducing bestpractice technologies - e.g. modern information and communications technologies - into their businesses and society countries that lag behind the leading productivity countries should succeed in gradually closing that gap. That process was characteristic of the development in Germany compared with the United States in past decades, but it has evidently faltered now. The productivity gap is growing again. At the same time other OECD and newly industrialised countries are catching up with Germany. So Germany is under pressure from two sides. The productivity gap that has been opening since the mid-1990s is putting Germany at a disadvantage in the international competition for inward investment, as on liberalized capital markets capital flows to where it can be used most productively, that is, at the highest rate of return. With the opening of markets in the newly industrialised countries, the political change in eastern Europe since the early 1990s and the resultant growing integration in the world economy Germany now has to maintain its position as a location for production in face of more intensive competition worldwide. High labour productivity is an essential location factor. If there are insufficient incentives to invest capital in highly productive jobs in Germany unemployment will rise rapidly while wages stagnate, as the low level of investment in the domestic economy makes progress in productivity relatively modest. Hence a low level of productivity can easily lead to a low level of growth with rising unemployment. The separation of short-term fluctuations in productivity from the medium to long-term trend in Germany compared with the United States has already been analyzed in an earlier study. However, at that time it was not possible to use the revised data of the national accounts for Germany as these were only published by the Federal Statistical Office in April this year.4 The introduction of chain indexes5 and hedonic methods6 in calculating the domestic product involved considerable methodological changes, and the implications of these for the determination of the short and medium-term productivity trends in Germany and the United States will be examined in this paper.
Keywords: 330